Characterization and properties of plasma electrolytic oxidation coating on low carbon steel fabricated from aluminate electrolyte. (October 2017) - Yang, Wenbin; Li, Qingbiao; Liu, Weimin; Liang, Jun; Peng, Zhenjun; Liu, Baixing
Abstract: Plasma electrolytic oxidation (PEO) coating was prepared from aluminate electrolyte on low carbon steel. The structure, composition, microhardness, anti-wear and anti-corrosion properties of the PEO coating were explored. The results show that the PEO coating possesses a uniform and dense structure and is mainly composed of α-Al2 O3 as well as some γ-Al2 O3 and Fe3 O4 . The PEO coating exhibits lower friction coefficient and wear rate than that of uncoated low carbon steel under dry sliding condition. The corrosion potential of coated sample shifts toward positive direction by 380 mV and the corrosion current density decreases by 2 orders of magnitude. Therefore, the PEO coating prepared from aluminate electrolyte can offer a good protection to low carbon steel from wear and corrosion. Highlights: A desirable aluminate electrolyte is used to prepare PEO coating on low carbon steel. Micropores are blocked by reaction products. The PEO coating is of dense structure and high hardness. The wear and corrosion resistance of low carbon steel are significantly improved.